2023
DOI: 10.1038/s41598-023-33333-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of rotenone binding to respiratory complex I depends on ligand flexibility

Abstract: Respiratory complex I is a major cellular energy transducer located in the inner mitochondrial membrane. Its inhibition by rotenone, a natural isoflavonoid, has been used for centuries by indigenous peoples to aid in fishing and, more recently, as a broad-spectrum pesticide or even a possible anticancer therapeutic. Unraveling the molecular mechanism of rotenone action will help to design tuned derivatives and to understand the still mysterious catalytic mechanism of complex I. Although composed of five fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In addition, the mRNA levels of mitoferrin 1 , mitoferrin 2 , and TFR were not affected by either rotenone and/or NaHS. Mitochondrial complex I activity has the largest number of iron-sulfur (Fe-S) cluster-containing proteins in the electron transport chain, which is known to be inhibited by rotenone [ 26 ]. ACO contains a [4Fe-4S]-cluster and is an essential enzyme in the citric acid cycle [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the mRNA levels of mitoferrin 1 , mitoferrin 2 , and TFR were not affected by either rotenone and/or NaHS. Mitochondrial complex I activity has the largest number of iron-sulfur (Fe-S) cluster-containing proteins in the electron transport chain, which is known to be inhibited by rotenone [ 26 ]. ACO contains a [4Fe-4S]-cluster and is an essential enzyme in the citric acid cycle [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of labile iron would induce oxidative stress, leading to mitochondrial damage, lipid peroxidation, and eventually ferroptosis [ 23 , 24 ]. Rotenone, a broad-spectrum pesticide, is a second-class hazardous agent for humans and is often used by researchers to mimic ischemic cell damage [ 25 , 26 , 27 ]. Many studies have shown that rotenone inhibits complex I in the mitochondrial ETC, leading to the disruption of ATP generation and initiation of cell death [ 25 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, WT cells were no longer protected from 1µM rotenone by MLi2. As 1 µM rotenone is likely approaching near complete complex I inhibition 67 , we suspect that overt toxicity overwhelms the protective effect of LRRK2-mediated effects such as improved mitochondrial clearance. However, as most exposures associated with PD likely happen at low doses over chronic periods 1,4,7,8,64,68,69 , LRRK2 could be involved in crosstalk with pathways triggered in parallel by environmental risk factors 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that these four binding sites share some common amino acid residues, which are conserved in various species ( Figure 4 A, blue dotted box) and likely to be conserved binding sites for TAO inhibitors ( Figure 7 K). The binding mechanism of rotenone to respiratory complex I is contingent upon the flexibility of the ligand; 176 it is also worthy to investigate the correlation between mechanism of this site and the flexibility of its ligands.…”
Section: Inhibitors Of Aoxmentioning
confidence: 99%